Time to Reload: The Harms of the Federal Felon-in-Possession Ban in a Post-Heller Worl - Sherwood, Zach (2021)
Federal law permanently prohibits anyone who has been convicted of a felony from possessing a firearm. Keeping lethal weapons out of the hands of those who pose a risk to public safety is no doubt a worthy policy goal. But the federal felon-in-possession ban is blunt, punitive, and supremely damaging to the ex-felons who fall within its ambit. The statute’s sweeping scope ensures that any ex-felon who possesses any firearm for any length of time for any reason can be swiftly and harshly punished. And it indiscriminately targets conduct that is often neither harmful nor criminal. The felon-in-possession ban gained constitutional significance following the Supreme Court’s landmark decision in District of Columbia v. Heller . The Heller Court recognized for the first time an individual Second Amendment right to possess a firearm for self-defense in the home. Yet by imposing substantial criminal liability on any form of firearm possession by an ex-felon, the felon-in-possession ban categorically strips a sizable portion of Americans of this very same right. This Note argues that it is high time to rethink the federal felon-in-possession ban’s role in a post-Heller world. It argues that the statute’s expansive reach is poorly tailored to addressing gun violence and highlights the weak doctrinal foundation on which the felon-in-possession ban is built. But this Note goes further than most existing scholarship by also examining the tangible, on-the-ground harms that the felon-in-possession ban inflicts on ex-felons and their communities—from needlessly complicating ex-felons’ reintegration into society, to burdening the Second Amendment rights of nonfelon family members, to effectively disarming large swaths of communities of color. Change is needed, and this Note recommends statutory reforms and constitutional challenges that would circumscribe the felon-in-possession ban’s scope